THE CHOSEN CLASSICAL AND NON-CLASSICAL ALGORITHMS IN THE GEODETIC MEASUREMENTS OF DISPLACEMENTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
The approach to analysing the measurement results of a levelling network which was established to identify the vertical displacements of the earth dam crone of a waste pond was presented in the paper. The obtained measurement results carried out by a precise levelling method were used in determining the precise displacements of the controlled points in the time function. The non-linear models of a kinematic network were applied to describe the displacements. A numerical evaluation of periodic measurement results was carried out by classical algorithms and neural networks. The neural networks recognized as the sophisticated modelling techniques were able to copy the non-linear functions.